Hot Corrosion Studies on Dissimilar Weldments C-22 and AISI 316L in the Molten Salt K2SO4 + 60%wt NaCl Environment. (2018) - Muthu, S.M.; Mohana Bharathi, C.; Vishal Gukhan, N.; Vignesh Kumar, S.; Venkatesh Kannan, M.; Arivarasu, M.; Manikandan, M.; Arivazhagan, N.
Abstract: High temperature corrosion of weldments is a major obstacle in various industrial applications such as gas turbines, boilers, diesel engines and furnaces .The materials are subjected to hot corrosion when they are working at elevated temperature. The objective of this work, to investigate the high temperature corrosion on activated fiux TIG welded C-22 and AISI 316 in eutectic mixture of K2 SO4 -60%NaCl environment at 650°C. After hot corrosion study, the weight gain was observed from thermo gravimetric analysis and the corrosive products were identified on the scale using XRD, SEM and EDAX analysis.. From the results of experiments, Cr2 O3 acts as a protective oxide layer of C-22 side which protect the surface from the molten salt environment at high temperature.